2021
DOI: 10.3390/socsci10110406
|View full text |Cite
|
Sign up to set email alerts
|

Transition from University to the Labour Market: The Impact of Personal Variables in Graduates’ Perceptions of Self-Efficacy

Abstract: The transition from university to the labour market is a crucial period for graduates. It is typically characterized by a high degree of uncertainty. Self-efficacy may be a determinant in the process, but the research so far has only considered students or graduates shortly after graduation, strongly compromising its conclusions on the findings. This study aims at exploring the variables which explain the different levels of self-efficacy of graduates in transition to the labour market. A total of 694 graduate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…The primary goal will be to produce competitive university graduates from tertiary educational institutes who can overcome unexpected and anticipated obstacles, and turn them into a source of development and differentiation for their organizations through the utilization of the skills they have gained through education and training. As a result, in post-COVID-19 periods, academic competence alone will no longer be sufficient in the eyes of employers for employing university graduates, and without proper competency and skills development, university graduates will fail to secure future employment in post-COVID periods (Buheji and Buheji 2020;Paulos et al 2021). However, multiple works over the year by Shohel et al (2021), Monem andBaniamin (2010), andHossain et al (2016) have shown that the higher educational (HE) institutes in the country are still following outdated curriculums and have not adopted the use of ICT in education.…”
Section: Need Of Skills Development For Future Employabilitymentioning
confidence: 99%
“…The primary goal will be to produce competitive university graduates from tertiary educational institutes who can overcome unexpected and anticipated obstacles, and turn them into a source of development and differentiation for their organizations through the utilization of the skills they have gained through education and training. As a result, in post-COVID-19 periods, academic competence alone will no longer be sufficient in the eyes of employers for employing university graduates, and without proper competency and skills development, university graduates will fail to secure future employment in post-COVID periods (Buheji and Buheji 2020;Paulos et al 2021). However, multiple works over the year by Shohel et al (2021), Monem andBaniamin (2010), andHossain et al (2016) have shown that the higher educational (HE) institutes in the country are still following outdated curriculums and have not adopted the use of ICT in education.…”
Section: Need Of Skills Development For Future Employabilitymentioning
confidence: 99%
“…Giret (2011), por sua vez, centrou a sua análise na forma como a formação superior pode contribuir para facilitar a transição, tendo em conta características da formação do estudante como o tipo de curso ou o grau obtido. Referem-se, também, estudos que procuraram analisar o contributo dos estágios curriculares para a perceção que os diplomados têm sobre o mercado de trabalho e acerca da sua preparação para a transição (Silva et al, 2016;Tsai et al, 2017), bem como para a perceção sobre a autoeficácia na procura de emprego (Paulos et al, 2021).…”
Section: Introductionunclassified